Laser-induced short-range disorder in aluminum revealed by ultrafast electron diffuse scattering - Zhu, Pengfei; Chen, Jie; Li, Runze; Chen, Long; Cao, Jianming; Sheng, Zhengming; Zhang, Jie (Applied physics letters, 2013)
We report ultrafast electron diffuse scattering intensity (DSI) measurement in order to study the structural response of aluminum to femtosecond laser excitation. In this measurement, the evolutions of DSI and Bragg peak intensities after the laser excitation are measured and compared in the time domain. Their differences suggest that two kinds of lattice disorder, short-range and long-range, are triggered simultaneously. The former, induced by electron excitation, arises and decays with a faster rate than the latter which is subject to lattice heating. The results presented show that the time-resolved DSI measurements provide complementary insights to the ultrafast diffraction measurements.